Ciliated Muconodular Papillary Tumors of the Lung: Distinct Molecular Features of an Insidious Tumor - Yang, Xinxin; Hou, Yunjing; Geng, Jiashi; Geng, Jingshu; Meng, Hongxue (Frontiers in Genetics, 2020)
Introduction Ciliated muconodular papillary tumors (CMPTs) are rare special peripheral pulmonary nodule composed of different cell proportions, characterized by papillary structures and significant alveolar mucus. Because of their rarity, underrecognized processes, the full range clinical course and histogenesis of CMPTs remains uncertain. Methods Molecular features of 5 CMPTs cases (one case with mucinous adenocarcinoma simultaneously) were observed by whole exon gene detection. The histological features of CMPTs and the development trends of three major constituent cells were studied by immunohistochemistry and PCR. Results NGS revealed 77 gene mutations in the patient’s tumor tissue and 31 mutations in the border tissue. TMB of CMPT tends to TMB of cancer tissues, and both are higher than normal tissues, CMPT share the same phylogenetic tree with cancer tissues. Moreover, PDL1, B7H3, and B7H4 were overexpressed in high columnar cells and eosinophilic ciliated cells of CMPT, tends to cancer tissues, while LAG3 and siglec15 were not found in CMPT. Conclusion The high prevalence of driver gene mutations in CMPTs, similar TMB and phylogenetic tree with cancer tissues indicate their malignant potential. Distinct molecular and immune check point features of each component support the notion that ciliated columnar cells in CMPT are insidious with immune escape.